Pengaruh Kualitas Layanan dan Harga Terhadap Keputusan Pembelian Merchandise Jkt48 Pada Komunitas Sumber Rezeki - Afi Sintia Lara (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The increasing interest in JKT48 merchandise has led to a high level of purchasing activity among fans. In this context, service quality and price are important factors that consumers consider before making a purchase. However, differences in consumer perceptions regarding the quality of service provided and the appropriateness of the prices offered may influence purchasing decisions. Therefore, this study aims to analyze the effect of service quality and price on purchasing decisions of JKT48 merchandise among members of the Sumber Rezeki Community. This research employed a quantitative approach using a survey method through questionnaires distributed to respondents who had purchased or were familiar with JKT48 merchandise. The population consisted of 900 community members, while the sample comprised 277 respondents selected using the Slovin formula and purposive sampling technique. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination with the assistance of IBM SPSS Statistics version 29. The results indicate that service quality and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. Therefore, improving service quality and setting appropriate prices can enhance consumers’ purchasing decisions regarding JKT48 merchandise